Origin and evolution of lepidopteran sex chromosomes(鳞翅目昆虫性染色体的起源与演化) - 胡竞衡(HU Jingheng); 罗惠(LUO Hui); 陈曦(CHEN Xi); 李飞(LI Fei) (浙江大学学报. 农业与生命科学版)
Lepidoptera, which include moths and butterflies, play important roles in biodiversity, and many species are important agricultural pests that damage a wide range of crops, resulting in substantial economic losses to agriculture. This review summarized recent advances in the origin and evolution mechanisms of lepidopteran sex chromosomes, with a particular focus on two hypotheses for the origin of sex chromosomes, three origin models for W chromosome, and the impact of the “faster-Z effect” on Z chromosome evolution. In-depth research on lepidopteran sex chromosomes not only helps reveal the mechanisms of sex determination but also provides new theoretical foundations and practical strategies for pest control. This review aims to provide valuable insights for both basic research on lepidopteran sex chromosomes and pest control. . 鳞翅目昆虫（包括蛾类和蝶类）在生物多样性中占据着重要的地位，其中很多种类是重要农业害虫，危害多种农作物，对农业经济造成重大损失。本文综述了鳞翅目昆虫性染色体的起源与演化机制等研究进展，重点讨论了性染色体的2种起源假说、W染色体的3种起源模式和“快速Z效应”对Z染色体演化的影响。深入研究鳞翅目昆虫的性染色体不仅有助于揭示性别决定机制，还能为害虫防治提供新的理论基础和应用策略。本综述旨在为鳞翅目昆虫性染色体的基础研究和害虫防治提供有益的参考和启示。